Soft Target Hardening : Protecting People from Attack - Hesterman, Jennifer; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
The US government spends billions of dollars to secure strategic and tactical assets at home and abroad against enemy attack. However, as "hard targets" such as military installations and government buildings are further strengthened, vulnerable soft targets are increasingly in the crosshairs of terrorists and violent criminals. Attacks on crowded spaces such as churches, schools, malls, transportation hubs, and recreational venues result in more casualties and have a powerful effect on the psyche of the populace. Soft Target Hardening: Protecting People from Attack, Second Edition, continues the national dialogue started by the first edition by providing case studies, best practices, and methodologies for identifying soft target vulnerabilities and reducing risk in the United States and beyond. Soft target attacks steadily climbed in number and scale of violence since the first edition of this book. New tactics emerged, as terrorists continually hit the "reset button" with each attack. In this volatile, ever-changing security environment, plans to protect people and property must be fluid and adaptable. Along with new hardening tactics, such as the use of tactical deception to disguise, conceal, and divert, the author has updated the text with new case studies to reflect and respond to the fast-moving transformation in methods from more complex and organized forms of terror to simpler, yet still-devastating approaches. This book is a must-read for those who secure, own, and operate soft target facilities, and for citizens who want to protect themselves and their families from attack.
Preface; The Author; 1. Soft Targets 2.The Psychology of Soft Target and Our Unique Vulnerability 3.International Terror Groups: Propensity and Ability to Mount Soft Target Attacks 4.Domestic Terrorism and the Homegrown Threat 5. Soft Target Threat Assessment: Schools, Churches, and Hospitals 6.Soft Target Threat Assessment: Malls, Sporting Events, and Recreational Venues 7.New Tactics and Emergent Threats 8.Soft Target Hardening and the Human Element 9.Deterring and Mitigating Attack 10.Twenty Takeaways About Soft Target Hardening.
Includes bibliographical references and index.
Also available in print format.
Keywords: A Current Assessment of the Motivations and Capabilities of Parties Most Likely to Perpetrate a Soft Target; Church security; Emergency response; Emergent Soft Target Tactics; General Soft Target Hardening Training and Tactics; Hospital security; Introduction to the Concept of Soft Targets; Risk management; School security; Soft target attack; Sports and recreation security; Target hardening; The Unique Vulnerability of the U.S. Due to Our Culture and History; Vulnerability assessment; Terrorism -- Prevention; United States; Domestic terrorism; Threat (Psychology); Electronic books